Automatic Generation Tool of FPGA Components for Robots - OHKAWA, Takeshi; MATSUMOTO, Takuya; YOKOTA, Takashi; YAMASHINA, Kazushi; OOTSU, Kanemitsu (IEICE Transactions on Information and Systems, 2019)
In order to realize intelligent robot system, it is required to process large amount of data input from complex and different kinds of sensors in a short time. FPGA is expected to improve process performance of robots due to better performance per power consumption than high performance CPU, but it has lower development productivity than software. In this paper, we discuss automatic generation of FPGA components for robots. A design tool, developed for easy integration of FPGA into robots, is proposed. The tool named cReComp can automatically convert circuit written in Verilog HDL into a software component compliant to a robot software framework ROS (Robot Operation System), which is the standard in robot development. To evaluate its productivity, we conducted a subject experiment. As a result, we confirmed that the automatic generation is effective to ease the development of FPGA components for robots.